2014
DOI: 10.18632/oncotarget.2500
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of RAC1 GTPase sensitizes pancreatic cancer cells to γ-irradiation

Abstract: Radiation therapy is a staple treatment for pancreatic cancer. However, owing to the intrinsic radioresistance of pancreatic cancer cells, radiation therapy often fails to increase survival of pancreatic cancer patients. Radiation impedes cancer cells by inducing DNA damage, which can activate cell cycle checkpoints. Normal cells possess both a G1 and G2 checkpoint. However, cancer cells are often defective in G1 checkpoint due to mutations/alterations in key regulators of this checkpoint. Accordingly, our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 95 publications
2
39
0
8
Order By: Relevance
“…Rac1 overexpression has been found in various types of cancer, such as lung cancer, gastric cancer, pancreatic cancer, bladder cancer and breast cancer 43, 44, 45, 46, 47. Moreover, activation of Rac1 can increase cancer cell migration, adhesion, invasion, proliferation and metastasis 40, 44, 48, 49, 50.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 overexpression has been found in various types of cancer, such as lung cancer, gastric cancer, pancreatic cancer, bladder cancer and breast cancer 43, 44, 45, 46, 47. Moreover, activation of Rac1 can increase cancer cell migration, adhesion, invasion, proliferation and metastasis 40, 44, 48, 49, 50.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the co-occurrence of alterations in MAGE-A9 and Rac1 is highly significantly associated with poorer overall survival (median survival in the altered group: 35.45 months; in the unaltered group: 67.81 months; P=0.00299) in HNSCC (42,43). Rac1 is a known factor contributing to chemoresistance and radioresistance, particularly in HNSCC (44)(45)(46).…”
Section: Discussionmentioning
confidence: 97%
“…As illustrated in Figure 1, Yan and colleagues, reported RAC1 (Ras-related C3 botulinum toxin substrate 1) as a potential target to reduce radioresistance in breast cancer cells (7) as well as pancreatic cancer cells (8). Rac1, a member of Rho family GTPase, functions as a binary molecular switch by cycling between an inactive GDP-bound and an active GTP-bound state.…”
mentioning
confidence: 99%
“…Rac1 GTPase is overexpressed or hyperactivated in various types of tumors and implicates in tumorigenesis, angiogenesis, invasion and metastasis (9). It has been repeatedly reported that Rac1 can be activated by IR treatment in some types of tumor cells, including breast cancer (10), pancreatic cancer (8), and head and neck squamous cell carcinoma (7) and is involved in the formation of radioresistance. In 2012, Yan and colleagues reported that IR induced G2/M checkpoint arrest through activation of ATM/ATR pathway and inhibition of Cdc25 phosphatase in breast cancers, but accompanied with the activation of ERK1/2 signaling, suggesting a potential survival signal contributing the development of radioresistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation